UNIT 8.11 Molecular Cytogenetic Analysis of Telomere Rearrangements. (20th January 2015) - Martin, Christa Lese; Ledbetter, David H.
Abstract : Genomic imbalances involving the telomeric regions of human chromosomes, which contain the highest gene concentration in the genome, are proposed to have severe phenotypic consequences. For this reason, it is important to identify telomere rearrangements and assess their contribution to human pathology. This unit describes the structure and function of human telomeres and outlines several methodologies that can be employed to study these unique regions of human chromosomes. It is a revision of the original version of the unit published in 2000, now including an introductory section describing advances in the discipline that have taken place since the original publication. © 2015 by John Wiley & Sons, Inc.